Sex bias in basic science and translational otolaryngology research. (8th November 2018) - Stephenson, Elizabeth D.; Farzal, Zainab; Kilpatrick, Lauren A.; Senior, Brent A.; Zanation, Adam M.
Abstract : Objectives/Hypothesis: Recent studies revealed sex bias in surgical research. Although many diseases exhibit sex‐based clinically relevant differences, otolaryngology research has not been evaluated for sex reporting and sex‐based analysis. We postulate that a similar bias is prevalent in otolaryngology literature. Study Design: Literature review. Methods: Articles published from 2016 to 2017 in The Laryngoscope, Otolaryngology–Head and Neck Surgery, and JAMA Otolaryngology–Head and Neck Surgery were reviewed. Articles with animal subjects, human subject cells, or commercial cell lines were included. Data collected included study type, cell/animal sex, and sex‐based data analysis. Results: One hundred forty‐four basic/translational research articles were identified. Sixty‐nine (47.9%) of those lacked sex reporting. Of 75 studies that reported sex, 22 (29.3%) included both sexes, and 11 (14.7%) analyzed data by sex. One hundred five (72.9%) used animal subjects, of which 54 (51.9%) lacked sex breakdown. Among animal studies, 48/105 included only one sex, and three articles analyzed data by sex. Fifty‐four studies used commercial cell lines (N = 23) or human/animal subject cells (N = 31). Among cell groups, 28/54 (51.9%) were of unknown sex, and seven were single sex. Eight (14.8%) studies included data analysis by sex. Domestic studies exhibited a lower rate of sex reporting in both animal and cell studies, and a lower rate of sex‐based analysis in cell studies. Conclusions: Sex may influence outcomes significantly but is underreported and underanalyzed in basic/translational otolaryngology research. Because this research frequently lays the groundwork for clinical trials and standards of care, future research must address these sex‐based discrepancies. Level of Evidence: NA Laryngoscope, 129:613–618, 2019